2014
DOI: 10.1093/gbe/evu150
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Functional Diversification within Quasispecies

Abstract: According to quasispecies theory, high mutation rates limit the amount of information genomes can store (Eigen’s Paradox), whereas genomes with higher degrees of neutrality may be selected even at the expenses of higher replication rates (the “survival of the flattest” effect). Introducing a complex genotype to phenotype map, such as RNA folding, epitomizes such effect because of the existence of neutral networks and their exploitation by evolution, affecting both population structure and genome composition. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Although the high mutation rate occasionally leads to fitness loss through loss of the master sequence, the increased evolvability enables the population to quickly recover, hence keeping the fitness of the best individuals at the same level (and sometimes at a higher level) than that of the wild-type individuals that evolved under a constant mutation rate. Similar results have been obtained in another class of model studied in the course of the project: by evolving RNA sequences, E. S. Colizzi [8] has shown that the RNA structure (the equivalent of the genome structure in the RNA model) is selected such that the population contains an efficient proportion of mutated sequences and such that the mutants help the master sequence to thrive.…”
Section: Evolution Of Genetic Architecture and The Role Of Non-codingsupporting
confidence: 72%
“…Although the high mutation rate occasionally leads to fitness loss through loss of the master sequence, the increased evolvability enables the population to quickly recover, hence keeping the fitness of the best individuals at the same level (and sometimes at a higher level) than that of the wild-type individuals that evolved under a constant mutation rate. Similar results have been obtained in another class of model studied in the course of the project: by evolving RNA sequences, E. S. Colizzi [8] has shown that the RNA structure (the equivalent of the genome structure in the RNA model) is selected such that the population contains an efficient proportion of mutated sequences and such that the mutants help the master sequence to thrive.…”
Section: Evolution Of Genetic Architecture and The Role Of Non-codingsupporting
confidence: 72%
“…Put differently, when considering the long-term reproductive success of a lineage, the genotype of the ancestor contains more information than its phenotype alone, because it determines its position on the mutational landscape. This question of mutational landscape location as a selectable property of an individual is a much broader one, central to, for example, the theory of quasispecies (Eigen and Schuster 1977;Nowak 1992;Wilke et al 2001;Colizzi and Hogeweg 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our work also directly connects with studies considering division of labor, another kind of social interactions between individuals. For example, Colizzi and Hogeweg (2014) present an RNA-world model where one "master sequence" encodes all the information necessary to produce (via mutations) a full ecosystem. Similarly, Rainey and Kerr (2010) suggest that non-cooperative types may be seen as a germline, whose ability to form a cooperative soma can be subject to selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations